Temporal Regulation of Chromatin During Myoblast Differentiation - Harada, Akihito (Semin Cell Dev Biol, 2017)
The commitment to and execution of differentiation programs involves a significant change in gene expression in the precursor cell to facilitate development of the mature cell type. In addition to being regulated by lineage-determining and auxiliary transcription factors that drive these changes, the structural status of the chromatin has a considerable impact on the transcriptional competence of differentiation-specific genes, which is clearly demonstrated by the large number of cofactors and the extraordinary complex mechanisms by which these genes become activated. The terminal differentiation of myoblasts to myotubes and mature skeletal muscle is an excellent system to illustrate these points. The MyoD family of closely related, lineage-determining transcription factors directs, largely through targeting to chromatin, a cascade of cooperating transcription factors and enzymes that incorporate or remove variant histones, post-translationally modify histones, and alter nucleosome structure and positioning via energy released by ATP hydrolysis. The coordinated action of these transcription factors and enzymes prevents expression of differentiation-specific genes in myoblasts and facilitates the transition of these genes from transcriptionally repressed to activated during the differentiation process. Regulation is achieved in both a temporal as well as spatial manner, as at least some of these factors and enzymes affect local chromatin structure at myogenic gene regulatory sequences as well as higher-order genome organization. Here we discuss the transition of genes that promote myoblast differentiation from the silenced to the activated state with an emphasis on the changes that occur to individual histones and the chromatin structure present at these loci.